Hyaluronan receptor LYVE-1-expressing macrophages maintain arterial tone through hyaluronan-mediated regulation of smooth muscle cell collagen - Lim, H; Lim, S; Tan, C; Thiam, C; Goh, C; Carbajo, D; Chew, S; See, P; Chakarov, S; Wang, X; Lim, L; Johnson, L; et al. (Elsevier, 2018)
The maintenance of appropriate arterial tone is critically important for normal physiological arterial function. However, the cellular and molecular mechanisms remain poorly defined. Here, we have shown that in the mouse aorta, resident macrophages prevented arterial stiffness and collagen deposition in the steady state. Using phenotyping, transcriptional profiling, and targeted deletion of Csf1r, we have demonstrated that these macrophages—which are a feature of blood vessels invested with smooth muscle cells (SMCs) in both mouse and human tissues—expressed the hyaluronan (HA) receptor LYVE-l. Furthermore, we have shown they possessed the unique ability to modulate collagen expression in SMCs by matrix metalloproteinase MMP-9-dependent proteolysis through engagement of LYVE-1 with the HA pericellular matrix of SMCs. Our study has unveiled a hitherto unknown homeostatic contribution of arterial LYVE-1+ macrophages through the control of collagen production by SMCs and has identified a function of LYVE-1 in leukocytes.